Review of Option Pricing Literature and An Online Real-Time Option Pricing Application Development - Liu, Shu (2007)
The dissertation seeks to have an exploration into the most commonly used option pricing models. As we will see in the second chapters, the classic Black-Scholes model, the Jump Diffusion Model, Binomial Tree model, Monte-Carlo valuation and Finite Difference Method are widely used in option pricing. A significant number of empirical evidences in literature tested the validity of the models based on the historical data, rarely are based on the real-time data. This dissertation aims to combine the computational knowledge and option pricing literature, to investigate, design and implement a new option pricing application, which can process the real-time or slightly delayed market quotes to price the options. The application could help researchers to test the accuracy of the pricing model or their input volatility, and also can help investor to compare the market with the estimated price to discover the best investment moment. The discussion, methodology and testing are focused on the computational finance joint issues.